أحكام ضم الصغير في قانون الأحداث العراقي والأردني - الكوردي، أكرم زاده Alkourdi, Akram Zadah (مركز جيل البحث العلمي, 2018)
يتناول هذا البحث أحكام ضم الصغير في قانون الأحداث العراقي والأردني. والغرض منه هو بيان أوجه التشابه والاختلاف بين قانون الأحداث لكلا البلدين فيما يتعلق بموضوع الدراسة، بهدف الاستفادة من نقاط القوة في كل قانون. وفي سبيل تحقيق ذلك، استخدم الباحث المنهج الاستقرائي التحليلي، المقارن، والنقدي. واختتم البحث بنتائج وهي: التشابه بين القانونين في بعض المسائل، مثل شمول الطفل مجهول النسب بالضم، المتابعة الأسرية لطالبي الضم من قبل الباحث الاجتماعي بعد صدور قرار الضم، والاختلاف في مسائل أخرى. وبخصوص مسائل الخلاف، فإن كفة الرجحان كانت لصالح القانون الأردني في بعض المسائل، مثل عدم نسبة الطفل مجهول النسب إلى طالبي الاحتضان، وتحقيق الحرمة الشرعية للطفل داخل الأسرة. وفي مسائل أخرى، كفة الرجحان كانت لصالح القانون العراقي، مثل شمول الصغير يتيم الأبوين بالضم، وصدور قرار الضم بمرحلتين. وعليه، بإمكان المشرع الأردني الاستفادة من المشرع العراقي، والعكس صحيح حيث يمكن للمشرع العراقي الاستفادة من المشرع الأردني.
This research deals with the provisions of the annexation of minors in the Iraqi and Jordanian juvenile law. Its purpose is to clarify the similarities and differences between the law of juveniles of both countries in relation to the subject matter of the study, in order to take advantage of the strengths of each law. To achieve this, the researcher used the analytical, comparative, and analytical inductive method. The study concluded with results: the similarity between the two laws on certain issues, such as family follow-up of applicants for annexation by the social researcher after the issuance of the annexation decision, and differences in other issues. On the issues of disagreement, the case for argument was in favor of Jordanian law on certain issues, such as, The illegitimacy of an unknown child to the seekers nursery, and achieving the legitimate sanctity of the child within the family. On other issues, the balance was the odds in favor of Iraqi law, such as the inclusion of small orphan parents joinder, and the decision to annex in two phases. Thus, the Jordanian legislature can benefit from the Iraqi legislator, and vice versa where the Iraqi legislator can benefit from the Jordanian legislator.
Keywords: قانون الأحداث العراقي -- قانون الأحداث الأردني -- ضم الصغير -- الاحتضان -- الطفل مجهول النسب